Aid, terrorism, and foreign direct investment: Empirical insight conditioned on corruption control - Uchenna Rapuluchukwu Efobi; Simplice Asongu; Ibukun Beecroft (African Governance and Development Institute (AGDI), 2018)
This paper examines the effect of foreign aid in the terrorism-FDI nexus while considering the extent of domestic corruption-control (CC). The empirical evidence is based on a sample of 78 developing countries. The following findings are established: the negative effect of terrorism on FDI is apparent only in countries with higher levels of CC; foreign aid dampens the negative effect of terrorism on FDI only in countries with high levels of CC. The result is mixed when foreign aid is subdivided into its bilateral and multilateral components. Our findings are in accordance with the stance that bilateral aid is effective in reducing the adverse effect of terrorism on FDI. Multilateral aid also decreases the adverse effect of other forms of terrorism that can neither be classified as domestic nor as transnational. Policy implications are discussed.
Keywords: D74; F21; F35; 330; Conflict; Developing countries; Foreign investment; Foreign aid; Terrorism